The efficacy of erbium-doped yttrium aluminum garnet (Er:YAG) laser in the treatment of decreased sexual sensation: a randomized, placebo-controlled trial - Angkana Sathaworawong (2022)
Vaginal laxity, a common cause of decreased sexual sensation, is a common problem affecting the quality of life of women worldwide. Recently, lasers and energy-based devices (EBDs) have been applied in the treatment of this condition. The aim of this study was to compare the efficacy and safety of Er:YAG laser and placebo in treating decreased sexual sensation in Asians. Forty-two patients with decreased sexual sensation were randomized into 2 groups: intervention (laser treatment) and control (placebo treatment). Both groups received two treatments, at 1-month interval. Subjective and objective evaluations were done at baseline, 1-, 3-, and 6-month follow-ups. Pain score and adverse effects were also recorded. In the laser group, there was significant improvement in the patients’ vaginal tightness satisfaction at 1- and 3-month follow-ups (P = 0.002 and 0.004) and also in the patients’ overall satisfaction at 1- and 3-month follow-ups (P = 0.003 and 0.001). Pelvic floor muscle contraction was significantly better in the laser group after the first treatment (P = 0.043). No serious adverse effects were noted. Er:YAG laser provides improvement of sexual sensation for an average of 3 months following treatment. Mild and transient adverse effects such as leukorrhea, dryness, dysuria, vaginal itching, and spot bleeding were noted in the laser group, and these were not significantly different from the control group.